Quarantine preparedness - the missing factor in COVID-19 behaviour change? Qualitative insights from Australia - Angela Davis; Stephanie Munari; Joseph Doyle; Brett Sutton; Allen Cheng; Margaret Hellard; Lisa Gibbs (BMC, 2022)
Abstract Background A key feature of the global public health response to contain and slow the spread of COVID-19 has been community-based quarantine and self-isolation. As part of The Optimise Study, this research sought to understand the factors that influence people's ability to undertake home-based quarantine and isolation to contain the spread of COVID-19. Methods Semi-structured qualitative phone interviews (n = 25) were conducted by telephone with people who participated in community-based quarantine in Australia before 31 March 2020. The Capability Opportunity Motivation Behaviour model was used to conduct a thematic analysis. Results Participants required clear, accessible and trusted information to guide them in home-based quarantine and isolation. A sense of social responsibility and belief in the efficacy of the restrictions to reduce viral transmission aided their motivation. Access to essential needs, supportive living environments, and emotional support were required to adhere to restrictions, but few were prepared. Conclusions Findings demonstrate that in addition to having the capability and motivation to adhere to restrictions, it is vital that people are also encouraged to prepare for the challenge to ensure access to physical, social and emotional support. Findings also illustrate the importance of engaging communities in planning and preparedness for quarantine and self-isolation public health responses.